ANALISIS HUBUNGAN SEKTOR KONSTRUKSI TERHADAP PDRB PADA PROVINSI DI INDONESIA - Elsa Amelia; Raja Masbar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2020)
Abstract This study aims to analyze the relationship of the construction sector to GRDP in provinces in Indonesia. In this study, the variables used are Construction, Labor, Investment and GRDP variables. This research was conducted to examine the impact and relationship on construction, labor, investment on a national scale and per zone (West, Central, East) in a certain period of time against the GRDP in Indonesia. The data for this study uses panel data of 34 provinces in Indonesia in the period 2010-2017 using the fixed effect model (FEM). The results of the fixed model approach show that construction has a positive but not significant effect on GRDP and then Investment has a positive and significant effect on GRDP in Indonesia. It is hoped that this research can become a reference and appeal for the government to implement construction sector policies in an effort to increase GRDP in every province in Indonesia.Keywords: construction, labor, investment and GRDP